Efeito do oléo-resina de copaiba (Copaifera sp) sobre o desenvolvimento de obesidade e disfunção do tecido adiposo - Telles, Luciana Ortega (2021)
Obesity, a worldwide public health problem, is a chronic disease characterized by an excessive or abnormal body fat accumulation that may lead to adipose tissue dysfunction. Active compounds were described in copaiba oleoresin, obtained by different species of Copaifera a typical tree at the north of Brazil, which presents antiinflammatory, antimicrobial and antioxidant properties. However, there is no data regard the effects of copaiba oleoresin in adipose tissue. Thus, the aim of this study was to eveluate the effect of copaiba oleoresin on obesity development and adipose tissue dysfunction in high-sucrose diet feed rats. Male Wistar rats were randomly assigned for receiving standart diet (C, n=8), standart diet and 30% sucrose in the drinking water (S, n=8), and S + copaiba oleoresin (S+OC, n=8). Copaiba oleoresin was given at dose of 200 mg/kg/day by gavage for eigth weeks. C and S animals received vehicle, at equivalent volume, by gavage. At the end of experiment, animals were killed by decapitation, and blood samples and epididymal adipose tissue were collected for biochemists, inflammatory and oxidative stress determinations. Data were expressed as mean and standart deviaton. The comparison between groups was performed using one-way ANOVA complemmented post-hoc Student-Newman-Keuls's test, with significance level adopted at P<0.05. Chromatographic analysis identified markers of copaiba oleoresin, the β-caryophyllene and α-humulene. High-sucrose diet model was efficient to promote obesity, which was associated to increased fasting glycemia, dyslipidemia and insulin resistance, also increased interleukin (IL)-6 and IL-1β levels and oxidative stress in the adipose tissue from S animals. Copaiba oleoresin supplementation prevented weight gain, adiposity, insulin resistance and increased IL-1β levels, in addition, partially inhibited the increase of fasting glucose levels, dyslipemia and IL-6 in adipose tissue, and improved the antioxidant defense system in adipose tissue. Therefore, it is possible to conclude that copaiba oleoresin displays benefic effects, suggesting its use as a good strategy for prevention of obesity and its complications.